Evaluating the outcomes of an executive coaching programme in South Africa - Wallis, Elizabeth (My University, 2012)
The discipline of executive coaching in South Africa has emerged as a growing leadership development trend over the past 15 years. Organisations, whilst investing in executive coaching as a developmental tool, have begun to demand more reliable evidence as to the outcomes and return on their investment yielded by executive coaching. This research project set out to identify the coachee reported outcomes of an executive coaching programme within South Africa. To this end, an existing database of semi-structured interviews was used, provided by an executive coaching firm, Change Partners. A qualitative research methodology was adopted to code the data through the use of thematic content analysis. Two independent raters were used to code the data to ensure objectivity and reliability. Twelve outcomes were revealed during the research process with varying degrees of frequency. Six outcomes, identified in the literature review, were in turn supported by the outcomes of the content analysis. An additional six outcomes were identified by the raters during the content analysis that were not identified in the literature review. These outcomes have been discussed with reference to the relevant literature and the results of the analysis respectively. Suggestions for future research as well as recommendations to key stakeholders have been made.
MBA thesis - WBS
Keywords: Executive coaching; Coaching